Foundations of Human Sociality: A Review Essay - Samuelson, Larry (Journal of Economic Literature, 2005)
This is a review article of Foundations of Human Sociality: Economic Experiments and Ethnographic Evidence from Fifteen Small-Scale Societies (Oxford University Press 2004) edited by Joseph Henrich, Robert Boyd, Samuel Bowles, Colin Camerer, Ernst Fehr, and Herbert Gintis.